Parametric Analysis of a Steel Industrial Building Frame Considering Wind Load, Dampers and Bracings Using ETABS A Review - Swapnil Jain; Murlidhar Chourasiya; Rahul Satbhaiya (International Journal of Scientific Research in Civil Engineering, 2022)
In addition to gravity stresses, the building's structural structure must handle lateral loads caused by earthquakes and wind. A lateral load causes significant stresses and instability, which results in vibration and drift. If industrial steel structures are not designed to withstand lateral loads, they may collapse, resulting in the death or destruction of people or property. As a result, the structure must not only be strong enough to withstand gravity loads, but also stiff enough to withstand lateral forces. According to a review of the literature, LLRSS (Lateral load Resisting structural system) components such as base isolation and dampers are used to manage seismic vibration and lateral drift. In this paper presenting review of literatures related to analysis of steel building structures.
Keywords: Steel Frame Building; Viscous Damper; Bracing System Storey Drift; Displacement; Base Shear; ETABS